2018
DOI: 10.1007/s00586-018-5700-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spinal fusion length on proximal junction biomechanics: a parametric computational study

Abstract: The length of the instrumentation has an important effect on the proximal segment biomechanics. Despite the limitations of the current model, musculoskeletal modeling appears to be a promising and versatile method to support planning of spinal instrumentation surgeries in the future. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Clearly, PJK is a multifactorial problem where the health of the surrounding musculature, especially those in the thoracic spine, is important. 43,44 Given that paraspinal musculature in the thorax plays a vital role Figure 1E). The seated posture was achieved by seating each subject on the scan table where the backrest was setup 90 relative to its seat ( Figure 1F).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, PJK is a multifactorial problem where the health of the surrounding musculature, especially those in the thoracic spine, is important. 43,44 Given that paraspinal musculature in the thorax plays a vital role Figure 1E). The seated posture was achieved by seating each subject on the scan table where the backrest was setup 90 relative to its seat ( Figure 1F).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clinical studies by Yagi et al 42 suggested that 41% of patients post lumbar degenerative scoliosis surgery, developed progressive global kyphosis in the thorax. Clearly, PJK is a multifactorial problem where the health of the surrounding musculature, especially those in the thoracic spine, is important 43,44 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] A plethora of literature exists on the clinical and radiographic risk factors for PJK. 3,[7][8][9][10][11][12][13][14][15][16][17][18] However, prevention of PJK remains unsolved and is still a relatively common postoperative complication.…”
Section: Introductionmentioning
confidence: 99%
“…This has even been shown to cause kyphosis or failure of the proximal junction. 19,20 In this experiment, the increase in the displacement of the adjacent segments after multisegment fixation under external force loading can also be explained by the stress concentration theory. 21 This means that when one or more spinal segments are fixed, the amount of deformation of the fixed segment will decrease or disappear and can only be transferred to the upper and lower segments.…”
Section: The Influence Of Different Fixed Lumbar Vertebrae Segments On Adjacent Segmentsmentioning
confidence: 68%